2021
DOI: 10.24815/siele.v8i1.18131
|View full text |Cite
|
Sign up to set email alerts
|

The listening skill of autistic students in learning English through total physical response

Abstract: This study analyses how a teacher at SMPLB-CD YPAC (Foundation for Children with Disabilities), Banda Aceh, Indonesia, teaches English listening using the Total Physical Response (TPR) method to autistic students. In this method, a teacher instructed the students to act as modelled by the teacher. Students are considered to have good listening comprehension if they understood the teacher’s commands and imitated the act. This research is qualitative to describe the application of the TPR method in teaching Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Based on the literature review and results, the authors agree with the affirmations of Nafkhatul and Taranindya-Zulhi (2017) and Sari (2021) concerning Total Physical Responds is a methodology that promotes the articulation of learners' thought and body movements for activating the process of learning.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Based on the literature review and results, the authors agree with the affirmations of Nafkhatul and Taranindya-Zulhi (2017) and Sari (2021) concerning Total Physical Responds is a methodology that promotes the articulation of learners' thought and body movements for activating the process of learning.…”
Section: Discussionsupporting
confidence: 77%
“…It can help students memorize new language patterns, facilitate the assimilation of grammar rules, and relax after mastering a complex topic without departing from the main lesson's topic (Vishnevskaia and Zhou, 2019). Therefore, teachers need to provide feedback for the students to help them learn from their mistakes (Sari et al, 2021).…”
Section: Children's Motivation For Learning a Foreign Language Using ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, with the rapid development of the Internet of ings, edge computing has been widely used in various fields, such as the Internet of Vehicles, wireless sensors and actuators, smart homes, and software-defined networks. In the future development, edge computing will complement and organically integrate with other computing and will be widely used in more industries and fields, providing an ideal software and hardware support platform for information processing in the Internet of ings era [18,19] [20]. However, generating huge data also brings huge challenges to data processing.…”
Section: English Learning System Constructionmentioning
confidence: 99%
“…Furthermore, researches on teaching students with autism in schools have been conducted many times in various fields of study. Some of them were conducted by (Maulidiyah & Thamrin, Nani Ronsani, 2023;Padmadewi & Artini, 2017;Romadlon, 2017;Sari et al, 2021;Susanti, 2024), etc. (Sari et al, 2021) found that the use of the (2024), 7 (1): 161-167…”
Section: Introductionmentioning
confidence: 99%